Transient upregulation of protein kinase C in pressure-overloaded neonatal rat myocardium - Hamplová, Blanka; Novák, František; Kolář, František; Nováková, Olga (Physiological research, 2010)
Protein kinase C (PKC) appears to play a significant role in the signal transduction of cardiac growth and development. The aim of this study was to determine changes in the total PKC activity and the expression of PKC isoforms alpha, delta and epsilon in the rat heart that was affected by pressure overload imposed at postnatal day (d) 2. Three groups of Wistar rats were employed for the experiment: rats submitted to the abdominal aortic constriction (AC), sham-operated controls (SO) and intact controls. Animals were sacrificed at d2, d3, d5 and d10. The total PKC activity was measured by the incorporation of (32)P into histone IIIS and the expression of PKC was analyzed by immunoblotting in the homogenate of the left ventricular myocardium and in the cytosolic, membrane-enriched (10(5) g) and nuclear-cytoskeletal-myofilament-enriched (10(3) g) fractions. We observed the significant transient increase in both the total PKC activity and the expression of all isoforms at d5 (the third day after the operation) in the cardiac homogenate of AC rats as compared with SO animals. Aortic constriction did not significantly affect the distribution of activity and isoform abundance among individual cellular fractions except for PKCdelta, which increased significantly at d10 in the cytosolic fraction at the expense of the membrane-enriched fraction. It is concluded that PKCalpha, PKCdelta and PKCepsilon undergo transient upregulation associated with the accelerated cardiac growth induced by pressure overload imposed in the very early postnatal period.
Keywords: financování organizované; Animals; novorozená zvířata; hypertenze; izoenzymy; Rats, Wistar; Blotting, Western; proteinkinasa C-alfa; Up-Regulation; Protein Kinase C-alpha; Time Factors; časové faktory; Animals, Newborn; Cell Fractionation; upregulace; Heart Diseases; krevní tlak; proteinkinasa C-epsilon; Financing, Organized; western blotting; Hypertension; Male; fosforylace; modely nemocí na zvířatech; Disease Models, Animal; krysa rodu Rattus; histony; Histones; frakcionace buněk; zvířata; mužské pohlaví; Isoenzymes; Protein Kinase C-epsilon; Blood Pressure; Myocardium; myokard; Protein Kinase C-delta; Protein Kinase C; Rats; proteinkinasa C-delta; Phosphorylation; proteinkinasa C; potkani Wistar; nemoci srdce